SOCIAL SCIENCES EDUCATION IN MULTICULTURAL EDUCATION AFTER POPULISM AND IDENTITY POLITICS IN INDONESIA - Marsini (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to analyze Social Sciences (IPS) in multicultural education after populism and identity politics in Indonesia. Populism and identity politics that occurred during Indonesian politics in 2014, 2017 and 2019 have damaged the harmony of national, state and social life. Even students are also the target of populism and identity politics which can be seen in expressions on social media or hate speech. The research method used is descriptive qualitative method with data collection through document analysis, literature study, observation and interviews. The results of the study show that the role, function and position of Social Sciences in schools is very strategic in minimizing the dangers and threats of populism and identity politics that target students in schools. Because the goal of IPS is to make students good citizens, develop critical thinking skills, develop intelligence and social skills, live up to moral values, and be multicultural. This is the strength of IPS in minimizing the dangers and threats of populism and identity politics, and schools and teachers should utilize the power of IPS to improve students' multiculturalism.